Successful erlotinib rechallenge after both gefitinib- and erlotinib-induced interstitial lung diseases - Arakawa, Nobuhito (Blackwell Publishing Ltd, 2013)
Epidermal growth factor receptor tyrosine kinase inhibitors, gefitnib and erlotinib, are effective for advanced nonsmall-cell lung cancer with epidermal growth factor receptor gene mutation. However, interstitial lung disease induced by these drugs is sometimes fatal, and discontinuation of the medication is the principle approach once this occurs. There are, however, some reports of cases in which rechallenge of gefitinib or erlotinib was successful, and it remains unclear when or how rechallenge should be attempted. We report the first successful case of erlotinib rechallenge after both gefitinib- and erlotinib-induced interstitial lung diseases. Our case suggests that, in interstitial lung disease induced by an epidermal growth factor receptor tyrosine kinase inhibitor, rechallenge with concurrent glucocorticoid administration and gradual increase of dosage could be a clinical option if imaging does not show a diffuse alveolar damage pattern, and if no alternative therapy is available.